2021
DOI: 10.1186/s12864-021-07723-x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of three maize husk traits by QTL mapping in a maize-teosinte population

Abstract: Background The maize husk consists of numerous leafy layers and plays vital roles in protecting the ear from pathogen infection and dehydration. Teosinte, the wild ancestor of maize, has about three layers of small husk outer covering the ear. Although several quantitative trait loci (QTL) underlying husk morphology variation have been reported, the genetic basis of husk traits between teosinte and maize remains unclear. Results A linkage populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…All statistical analyses were performed by using R Version 4.0.1 ( www.R-project.org ) as previously described ( Zhang et al., 2021 ; Zhang et al., 2022 ). The R ‘AOV’ function was used to estimate the variances of TOC.…”
Section: Methodsmentioning
confidence: 99%
“…All statistical analyses were performed by using R Version 4.0.1 ( www.R-project.org ) as previously described ( Zhang et al., 2021 ; Zhang et al., 2022 ). The R ‘AOV’ function was used to estimate the variances of TOC.…”
Section: Methodsmentioning
confidence: 99%
“…R Version 4.0.1 ( www.R-project.org ) was used to perform all statistical analyses as previously described (Zhang et al, 2021 ). The variances of SC were estimated by using the R ‘AOV' function.…”
Section: Methodsmentioning
confidence: 99%
“…The recessive mutation in milkweed pod1, encoding a KANADI protein, results in abnormal abaxial/adaxial patterning of both maize leaves and husk leaves (Candela et al, 2008). Although several quantitative trait loci underpinning multifaceted maize husk leaf traits have been identified by integrating linkage mapping analysis with genome-wide association studies (Cui et al, 2016(Cui et al, , 2018Jiang et al, 2020;Zhang et al, 2021), none of the genes underlying these loci have been identified.…”
Section: Introductionmentioning
confidence: 99%